THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1944)
Abstract It is not unusual for accounting teachers to stress knowledge as an important aspect of preparation for a career in professional accounting. And it is perhaps understandable that sometimes they may not show full appreciation of the existence of other factors besides technical competence. Accounting practitioners, on the other hand, often emphasize the fact that qualities other than technical competence contribute greatly to successful professional service. Perhaps they sometimes give the impression that personal factors are more important than technical preparation. In one occupation rating scale constructed from data supplied by twenty industrial and vocational psychologists, occupations of university professor, oculist, civil engineer, journalist are classified in the first category of high abstract intelligence. But no mention is made there of the certified public accountant (CPA) or his counterpart in industry, the controller. It is not necessary to assert that a CPA is the intellectual equal of an oculist, a journalist, an engineer, or a professor, in order to point out that there may be a real question here concerning the adequacy of sampling which omits an important occupation.